Fishermen and Farmers' Wives in Meeting the Needs of Family Life (A Case Study on a Family-family whose Husband has left behind in Morela Subdistrict Leihitu, Moluccas) - Soselisa, Hobarth Williams (Sangia Research Media and Publishing, 2020)
The effort of women as the head of the family ini fulfilling the necessities of life is a change in status/fungtion from a housewife to being the head of the family as a result of the conflict Mamala and Morela. With this change in status, he changed his role, namely as a father to children as well as breadwinner to meet the needs of family life. The purpose of this study is to describe and analyze the social, economic, psychological and spiritual conditions of the family after the departure of the husband and to provide an overview of the efforts made by women as the head of the family in meeting the needs of family life. This type of research is descriptive qualitative. Data collection methods, of observation, in-depth interview, FGD and documentation studies. Data was collected from bureaucrats, religious leaders. Traditional leaders, and women breadwinners. Efforts made by women to survive in fulfilling the necessities of life include trading (opening stalls, selling fish, meatballs and boiled noodles) seweing and working in beauty salons. The key factor for family survival in fulfilling life socially, economically, psychologically and spiritually is the family itself and environmental factors as well as determinants to be used by families to develop their businesses. Womens efforts in fulfilling the necessities of life are a form of independence, namely an attiude of confidence and willingnees to take the initiative to survive and not depend on other parties.